Wanprestasi Terhadap Perjanjian Sewa-Menyewa Rusunawa MBR Di Kota Gorontalo - Desya Natalia P. Wulungo; Mutia Cherawaty Thalib; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to discuss defaults in rental agreements for flats for low-income communities in the city of Gorontalo in light of law number 20 of 2011 concerning flats. By reviewing the issues regarding the form of implementation of the rental agreement and the legal consequences of non-performance in the agreement, this research can benefit from this. The method used in this research is an empirical legal research method. The results of this research suggest that it is necessary to provide legal education to flat tenants by implementing the contents of the rental agreement as well as the responsibility of the government as the manager of the flat, then carrying out good coordination between the relevant and authorized parties in resolving a case/case.